Spraying mortar for repairing concrete structure and preparation method thereof
By using phosphate cement and modifiers in spray mortar, the problems of insufficient sag resistance and bonding strength during facade/top repair in the prior art are solved, and efficient spraying construction and excellent durability are achieved.
Patent Information
- Application Number
- CN202510084171.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The prior art is difficult to meet the requirements of facade/top surface repair, especially during spraying construction, the sag resistance and bonding strength of conventional phosphate cement mortars are insufficient.
A spray mortar including phosphate cement, fine aggregates, blends, modifiers and additives is used to improve the consistency and sag resistance of the slurry through the compounding of phosphate cement and the use of modifiers.
It realizes efficient spraying construction, the slurry has good sag resistance and bonding strength, can be quickly restored to use, and has excellent crack resistance, salt freezing and steel bar corrosion resistance.
Smart Images

Figure BDA0005249628030000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to a spray mortar for repairing a concrete structure and a preparation method thereof, and can be particularly used for repairing a facade / ceiling. Background Art
[0002] Traditional cement-based materials have good plasticity. After being modified by adding cellulose ether, starch ether and other raw materials, they can obtain good anti-sagging properties and can maintain uniform distribution on vertical or inclined surfaces without flowing or sagging. Phosphate cement mortar not only has excellent bonding strength, high mechanical properties, good resistance to (salt) freezing and steel corrosion, but also has extremely low shrinkage and good volume stability, making it very suitable for rapid repair of cement concrete structures; however, conventional phosphate cement mortar has high viscosity and good fluidity, and cannot meet the requirements of facade / top surface repair.
[0003] Patent CN 106966687 B discloses a non-flowable, fast-setting, strong-bonding phosphate cement repair material and a preparation method thereof, which is composed of rubber powder, sand, magnesium oxide, ammonium dihydrogen phosphate, rubber powder, fly ash, sodium silicate, polypropylene fiber, retarder, polycarboxylic acid water reducer and water. The gel material is mainly rubber powder and supplemented by phosphate cement. It is mainly used for repairing bridge slabs or special locations on building facades after diseases occur. However, this solution can only be applied to manual plastering construction and is not suitable for spraying construction. Patent CN 109592959 B discloses an easy-to-construct high-bonding facade repair material and a preparation method thereof, comprising quartz sand, metal oxides, brucite powder, ammonium dihydrogen phosphate, talcum powder, silica fume, xanthan gum, air entraining agent, retarder and water, having good anti-sagging property and bonding strength, and being applicable to the repair of the top surface or facade of a structure; however, this technical solution has good wall-mounting performance and does not sag when manual plastering is used and the thickness of the one-time construction is relatively thin. However, when spraying is used, the anti-sagging property is significantly reduced, and the requirements for facade or top surface repair cannot be met. Summary of the invention
[0004] In view of the shortcomings of the current technical solutions, the purpose of the present invention is to provide a spray mortar for repairing concrete structures, which can be constructed by spraying, does not block pipes, has high construction efficiency, has good anti-sagging and cohesiveness, and has excellent comprehensive durability.
[0005] The second object of the present invention is to provide a method for preparing the spray mortar.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The present invention provides a spray mortar for repairing a concrete structure, wherein the spray mortar comprises the following raw materials in parts by weight:
[0008] 100 parts of phosphate cement, 20-150 parts of fine aggregate, 10-50 parts of admixture, 0.1-5 parts of modifier, 0.02-0.5 parts of additive, and 10-40 parts of water.
[0009] The phosphate cement is composed of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, metal oxides and borax, that is, the phosphate includes ammonium dihydrogen phosphate and potassium dihydrogen phosphate, and the molar ratio of ammonium dihydrogen phosphate to potassium dihydrogen phosphate is 1: (0-1); the metal oxide is magnesium oxide, and the initial setting time of the phosphate cement is greater than 20 minutes, the flexural and compressive strengths are greater than 3.5MPa and 20.0MPa respectively in 1 hour, and the flexural and compressive strengths are greater than 8.0MPa and 50.0MPa respectively in 28 days.
[0010] The fine aggregate is quartz sand, including any one of machine-made sand, washed sand and river sand; the silicon dioxide content in the quartz sand is greater than 96%, the mud content is less than 0.2%, and the maximum particle size is 0.6 mm.
[0011] The admixture comprises one or more of fly ash, silica ash, ultrafine fly ash, metakaolin and bentonite. The fly ash is primary or secondary low-calcium ash, and the silicon dioxide content in the silica ash is greater than 92%.
[0012] The modifier is one or more of polyacrylate resin, polysaccharide polymer and nano silicon dioxide.
[0013] The additive is one or more of melamine water reducer, naphthalene water reducer, sodium lignin sulfonate water reducer and calcium lignin sulfonate water reducer.
[0014] The water is tap water.
[0015] In order to achieve the above-mentioned purpose, the present invention also proposes a preparation and construction method of spray mortar: first, the modifier and the additive are mixed evenly, and a small amount of water is used to prepare an aqueous solution for use, then the phosphate cement, fine aggregate and admixture are dry-mixed evenly, and the remaining water is poured in and stirred for 2 to 3 minutes, and finally the aqueous solution is added and stirred for 1 minute to obtain the spray mortar.
[0016] Before construction, the surface of the concrete structure or wall should be cleaned first. The surface dust, moss, oil and other impurities can be washed away with a high-pressure water gun and dried in advance. If the exposed steel bars are rusted, they should be derusted first, and then the mortar sprayer should be used to evenly spray the mortar on the surface of the structure.
[0017] Preferably, the molar ratio of ammonium dihydrogen phosphate to potassium dihydrogen phosphate in the phosphate cement is 1: (0.1-0.8); the fine aggregate is machine-made quartz sand; the bentonite is organic bentonite; the modifier is a mixture of polysaccharide polymer (or polyacrylate resin) and nano-silicon dioxide; the additive is a mixture of melamine water reducer and wood calcium / wood sodium water reducer or naphthalene water reducer. Among them, phosphate cement adopts two compounding schemes of ammonium dihydrogen phosphate and potassium dihydrogen phosphate, which reduces the fluidity of cement itself while ensuring the strength of the material; by adding organic bentonite to the admixture, good thixotropy can be exhibited in the system; the modifier adopts a compound of polysaccharide polymer (or polyacrylate resin) and nano-silicon dioxide, which can increase the consistency and water retention of the slurry and further improve the thixotropy of the slurry; the additive is a mixture of melamine and wood calcium / wood sodium / naphthalene water reducer, which can not only reduce the viscosity of the slurry, but also improve the plasticity of the slurry. However, when a single modifier or a single additive is used, the anti-sagging performance of the slurry cannot achieve the best effect. When the water consumption is high or the repair thickness is large, there is still a phenomenon of dripping during the facade construction. When the modifier and the additive are compounded, the anti-sagging performance of the slurry has a qualitative leap, and the slurry is soft, with small internal shear force, and is easy to stir and construct.
[0018] Preferably, the spray mortar for repairing concrete structures comprises the following raw materials in parts by weight: 100 parts of phosphate cement, 30-110 parts of fine aggregate, 15-40 parts of admixture, 0.5-3 parts of modifier, 0.04-0.4 parts of additive, and 10-30 parts of water.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. The slurry has good plasticity and anti-sagging performance, and will not have defects such as teardrops, flowing or sagging. The slurry consistency can reach more than 80mm, and the internal friction resistance is small, which is very suitable for spraying construction;
[0021] 2. High bonding strength. Its bonding flexural strength with concrete structure can reach more than 8.0MPa. The damaged surface is on the original concrete specimen and can be integrated with the repaired surface.
[0022] 3. Rapid strength development and high comprehensive mechanical properties; the 1-hour flexural / compressive strength can reach more than 4.5MPa / 25.0MPa, and can be quickly restored to use; the 7-day flexural / compressive strength is greater than 10.0MPa / 50.0MPa, meeting the requirements of structural repair;
[0023] 4. Good durability. The spray mortar has good crack resistance, salt frost resistance and steel corrosion resistance. It is very suitable for the rapid repair of damaged areas on the facade / top surface of concrete structures such as exposed steel bars and salt frost erosion.
[0024] 5. Mechanical spraying is used for construction, which is simple, efficient, quality controllable, requires less labor and has lower construction costs. DETAILED DESCRIPTION
[0025] The present invention is described in detail below with reference to specific embodiments.
[0026] The consistency of spray mortar is tested using the consistency test in JGJ / T 70-2009 "Standard for Test Methods for Basic Properties of Building Mortar", and the arithmetic mean of the two test results is taken as the measured value, accurate to 1mm.
[0027] The anti-sagging performance is measured with reference to GB / T 9264-2012 "Evaluation of the anti-sagging property of paints and varnishes". The specific method is as follows: a test plate with a side length of 50 cm is prepared with ordinary cement concrete, and it is used after curing for 28 days. The floating dust on the surface is removed before the test. The test plate is placed vertically, and the repair mortar is sprayed evenly on the test plate. The spraying thickness is controlled by the number of spraying passes. After reading the spraying thickness measurement value with a vernier caliper, a horizontal thin line is immediately drawn across the test plate, about 250 mm from the top position. After drawing the horizontal line, the test plate is immediately checked for sagging marks (depending on the rheological properties of the repair mortar, sagging can be observed almost immediately after application, or it takes several minutes to observe). If the horizontal line moves, sagging occurs, and the defects such as teardrops, flow and sagging are evaluated in the entire test plate area, including the situation at the line mark.
[0028] The interfacial flexural strength is an effective way to characterize the bonding strength of the repair mortar. It is measured according to the method of JC / T 2537-2019 "Magnesium Phosphate Repair Mortar". The benchmark cement mortar block is made of 42.5 grade cement in accordance with GB 175. Before use, the benchmark cement mortar block should be polished with No. 200 sandpaper to remove the debris remaining on the contact interface. In the triple mold where the cement mortar block is placed in advance, pour the repair mortar mixture, evenly tamp with a plastering knife 15 times, manually shake it 5 times, and then use a scraper to smooth the mortar surface to make a test bonding specimen. The formed test bonding specimen is cured in the test environment for 1h and 7d, and its flexural strength is measured according to the mortar flexural strength test method. The flexural strength is used to represent the interfacial flexural strength, accurate to 0.1MPa.
[0029] The flexural and compressive strength are tested with reference to GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)".
[0030] The crack resistance is tested by simulating strong wind and dry environment to induce cracking. The spraying area tested is not less than 1m 2 , wind speed is 5m / s, humidity is below 10%, and it is placed in the test environment immediately after spraying construction, and the cracking situation before the repair mortar is completely hardened is recorded.
[0031] The anti-salt-freeze erosion performance was tested with reference to Appendix B of MH 5006-2015 "Technical Specifications for Construction of Cement Concrete Surface Layers at Civil Airports" - Test Method for Freeze-thaw Damage of Cement Concrete Against Deicing Fluid. The test erosion solution was a solution prepared with a mass ratio of 96% distilled water and 4% potassium formate. The diameter of the test mortar specimen was 150mm and the height was 100mm. The molding surface was the test surface. It was naturally cured for 7 days and then immersed in water for 4 days. The salt-freeze erosion performance test was then carried out. The amount of peeling per unit surface of the specimen after 30 freeze-thaw cycles was tested, accurate to 0.01kg / m 2 .
[0032] Example 1
[0033] A spray mortar for repairing concrete structures, comprising the following components in parts by weight:
[0033] 100 parts of phosphate cement, 80 parts of fine aggregate, 30 parts of admixture, 1.2 parts of modifier, 0.13 parts of additive, and 22 parts of water.
[0034] The molar ratio of ammonium dihydrogen phosphate to potassium dihydrogen phosphate in the phosphate cement is 1:0.2, the initial setting time of the phosphate cement is greater than 20 minutes, the 1-hour flexural and compressive strengths are greater than 3.5 MPa and 20.0 MPa respectively, and the 28-day flexural and compressive strengths are greater than 8.0 MPa and 50.0 MPa respectively; the fine aggregate is machine-made quartz sand; the admixture is a mixture of fly ash, ultrafine fly ash, and silica ash in a mass ratio of 1:1:1, the modifier is a mixture of polyacrylate resin and nano-silicon dioxide in a mass ratio of 2:1, the additive is a mixture of commercially available melamine water reducer and calcium lignin sulfonate water reducer in a mass ratio of 2:3, and the water is tap water.
[0035] The preparation method of the spray mortar is as follows: firstly, the modifier and the additive are mixed evenly, and a small amount of water is used to prepare an aqueous solution for standby use, then the phosphate cement, fine aggregate and admixture are dry-mixed evenly, and then the remaining water is poured in and stirred for 2 to 3 minutes, and finally the aqueous solution is added and stirred for 1 minute to obtain a spray mortar mixture.
[0036] Before spraying, the concrete structure surface or wall surface should be cleaned. The dust, moss, oil and other impurities on the surface can be washed away with a high-pressure water gun and dried. If the exposed steel bars are rusted, they should be rusted first, and then the mortar sprayer should be used to evenly spray the mortar on the concrete structure surface to be repaired. The performance test results are shown in Table 1.
[0037] Example 2
[0038] A spray mortar for repairing concrete structures, comprising the following components in parts by weight:
[0039] 100 parts of phosphate cement, 100 parts of fine aggregate, 36 parts of admixture, 1.5 parts of modifier, 0.16 parts of additive, and 23 parts of water.
[0040] The molar ratio of ammonium dihydrogen phosphate to potassium dihydrogen phosphate in the phosphate cement is 1:0.5, the initial setting time of the phosphate cement is greater than 20 minutes, the 1-hour flexural and compressive strengths are greater than 3.5 MPa and 20.0 MPa respectively, and the 28-day flexural and compressive strengths are greater than 8.0 MPa and 50.0 MPa respectively; the fine aggregate is washed quartz sand; the admixture is fly ash, ultrafine fly ash, silica fume, and bentonite mixed in a mass ratio of 1:1:1:0.5, and the bentonite is organic bentonite; the modifier is a mixture of polysaccharide polymer and nano silicon dioxide in a mass ratio of 2:1, the additive is a mixture of commercially available melamine water reducer and naphthalene water reducer in a mass ratio of 1:1, and the water is tap water.
[0041] The preparation method and construction method of the spray mortar are the same as those in Example 1, and the performance test results are shown in Table 1.
[0042] Example 3
[0043] A spray mortar for repairing concrete structures, comprising the following components in parts by weight:
[0044] 100 parts of phosphate cement, 40 parts of fine aggregate, 27 parts of admixture, 1.3 parts of modifier, 0.15 parts of additive, and 20.5 parts of water.
[0045] The molar ratio of ammonium dihydrogen phosphate to potassium dihydrogen phosphate in the phosphate cement is 1:0.7, the initial setting time of the phosphate cement is greater than 20 minutes, the 1-hour flexural and compressive strengths are greater than 3.5 MPa and 20.0 MPa respectively, and the 28-day flexural and compressive strengths are greater than 8.0 MPa and 50.0 MPa respectively; the fine aggregate is washed quartz sand; the admixture is a mixture of fly ash, ultrafine fly ash, silica fume, and metakaolin in a mass ratio of 1:1:1:0.5, the modifier is a mixture of polysaccharide polymer and nano-silicon dioxide in a mass ratio of 2:1, the additive is a mixture of commercially available melamine water reducer and sodium lignin sulfonate water reducer in a mass ratio of 2:3, and the water is tap water.
[0046] The preparation method and construction method of the spray mortar are the same as those in Example 1, and the performance test results are shown in Table 1.
[0047] Comparative Example 1
[0048] A spray mortar for repairing concrete structures, comprising the following components in parts by weight:
[0049] 100 parts of phosphate cement, 80 parts of fine aggregate, 35 parts of admixture, 2 parts of modifier, and 21 parts of water.
[0050] This comparative example does not contain any additives, the molar ratio of ammonium dihydrogen phosphate to potassium dihydrogen phosphate in the phosphate cement is 1:0.2, the initial setting time of the phosphate cement is greater than 20 minutes, the flexural and compressive strengths are greater than 3.5 MPa and 20.0 MPa in 1 hour, respectively, and the flexural and compressive strengths are greater than 8.0 MPa and 50.0 MPa in 28 days, respectively; the fine aggregate is washed quartz sand; the admixture is a mixture of fly ash, ultrafine fly ash, and silica ash in a mass ratio of 1:1:1, the modifier is a mixture of polysaccharide macromolecular polymer and nano-silicon dioxide in a mass ratio of 2:1, and the water is tap water.
[0051] The preparation method and construction method of the spray mortar are the same as those in Example 1, and the performance test results are shown in Table 1.
[0052] Comparative Example 2
[0053] A spray mortar for repairing concrete structures, comprising the following components in parts by weight:
[0054] 100 parts of phosphate cement, 50 parts of fine aggregate, 28 parts of admixture, 0.3 parts of additives, and 21 parts of water.
[0055] This comparative example does not contain any modifier, the molar ratio of ammonium dihydrogen phosphate to potassium dihydrogen phosphate in the phosphate cement is 1:0.5, the initial setting time of the phosphate cement is greater than 20 minutes, the flexural and compressive strengths are greater than 3.5 MPa and 20.0 MPa in 1 hour, respectively, and the flexural and compressive strengths are greater than 8.0 MPa and 50.0 MPa in 28 days, respectively; the fine aggregate is washed quartz sand; the admixture is a mixture of fly ash, ultrafine fly ash, silica fume, and bentonite in a mass ratio of 1:1:1:0.5, and the bentonite is organic bentonite; the additive is a mixture of commercially available melamine water reducer and sodium lignin sulfonate water reducer in a mass ratio of 2:3, and the water is tap water.
[0056] The preparation method and construction method of the spray mortar are the same as those in Example 1, and the performance test results are shown in Table 1.
[0057] Comparative Example 3
[0058] According to Example 1 of Patent CN 106966687 B, a non-flowable, fast-setting, strong-adhesive phosphate cement repair material and its preparation method, a phosphate cement-based rapid repair material was prepared. Although the mortar mixture has no flowability, it is relatively loose and has great resistance to surface construction. When the water consumption is increased by 2 times, the slurry has a certain cohesiveness, but still cannot meet the requirements of spraying construction. Specific test data are shown in Table 1.
[0059] Comparative Example 4
[0060] The facade repair material was prepared with reference to Example 4 of Patent CN 109592959 B, an easy-to-construct high-bonding facade repair material and its preparation method. When the surface was applied by plastering, the mixture was relatively soft and easy to construct, and had good anti-sagging performance, without obvious sagging. However, when spraying was used, the slurry had obvious sagging defects. For specific test results, see Table 1.
[0061] Comparative Example 5 is based on Example 1 without adding additives, and Comparative Example 6 is based on Example 1 without adding modifiers. Other preparation methods and construction methods are exactly the same as those of Example 1. The performance test results are shown in Table 1.
[0062] As can be seen from Table 1, the repair mortars of Examples 1 to 3 have significantly higher consistencies, softer slurries, and good anti-sagging properties, and no sag marks appear after three sprayings, indicating that even if the repair thickness is large, the repair mortar prepared by this scheme still has higher anti-sagging properties, and will not have teardrop-shaped, flowing and sagging defects, and can meet the repair requirements of conventional facades or top surfaces; although the repair mortars of Comparative Examples 1, 2 and 4 have lower consistencies and drier slurries, they still have defects such as sag marks, indicating that they cannot meet the requirements of facade repair under the conditions of spraying construction; Comparative Example 3 has very good anti-sagging properties, but the slurry is too dry, and even if the water consumption is greatly increased, it cannot meet the requirements of spraying construction, and when the water consumption is greatly increased, its comprehensive mechanical properties are too low to meet the repair requirements. In combination with Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 5 and Comparative Example 6, it can be seen that the anti-sagging performance of the repair mortar is not significantly improved by the single addition of the modifier, and the anti-sagging performance of the additive is improved, but there are still a few signs of sagging. Through the synergistic effect of multiple factors such as phosphate compounding, admixture optimization design, modifiers and additives, the anti-sagging performance of the repair mortar is significantly improved, and the slurry has a large consistency, small friction resistance, and is easier to spray and construct, achieving excellent results; at the same time, the repair material prepared by this technical solution has high interface bending and tensile strength and its own flexural and compressive strength, excellent crack resistance and resistance to salt frost erosion, which can meet the requirements for conventional concrete structure facade / top surface repair, and is particularly suitable for the rapid repair of facade / top surface areas such as bridge guardrails and piers that have been damaged by deicing salt / salt spray erosion in northern China.
[0063] Table 1
[0064] Note: ① The test environment temperature is 10°C, and the initial setting time of the repair mortars of all embodiments and comparative examples is greater than 20min; ② The repair mortars of all embodiments and comparative examples passed the crack resistance test, and no cracks appeared on the surface; ③ In the anti-sagging performance test, the test panels of Examples 1 to 3 were sprayed with repair mortar 3 times; Comparative Example 3 was applied to the test panel by manual smearing, and the test panels of the other comparative examples were sprayed with repair mortar once; ④ The water consumption of Comparative Example 3 was greatly increased, resulting in very low strength of the tested piece, and the test block could be broken by hand, so its interface flexural tensile strength, flexural compressive strength and salt-freezing erosion resistance were not tested.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A spray mortar for repairing concrete structures, characterized in that: The invention comprises the following components in parts by weight: 100 parts of phosphate cement, 20 to 150 parts of fine aggregate, 10 to 50 parts of admixture, 0.1 to 5 parts of modifier, 0.02 to 0.5 parts of additive and 10 to 40 parts of water; the modifier is one or more of polyacrylate resin, polysaccharide polymer and nano-silicon dioxide; the additive is one or more of melamine water reducer, naphthalene water reducer, sodium lignin sulfonate water reducer and calcium lignin sulfonate water reducer.
2. The spray mortar for repairing concrete structure according to claim 1, characterized in that: The phosphate cement comprises ammonium dihydrogen phosphate and potassium dihydrogen phosphate, wherein the molar ratio of ammonium dihydrogen phosphate to potassium dihydrogen phosphate is 1:(0-1); the initial setting time of the phosphate cement is greater than 20 minutes, the flexural and compressive strengths are greater than 3.5 MPa and 20.0 MPa in 1 hour, respectively, and the flexural and compressive strengths are greater than 8.0 MPa and 50.0 MPa in 28 days.
3. The spray mortar for repairing concrete structure according to claim 1, characterized in that: The phosphate cement comprises ammonium dihydrogen phosphate and potassium dihydrogen phosphate, wherein the molar ratio of ammonium dihydrogen phosphate to potassium dihydrogen phosphate is 1:(0.1-0.8).
4. The spray mortar for repairing concrete structure according to claim 1, characterized in that: The spraying mortar comprises the following components in parts by weight: 100 parts of phosphate cement, 30-110 parts of fine aggregate, 15-40 parts of admixture, 0.5-3 parts of modifier, 0.04-0.4 parts of additive, and 10-30 parts of water.
5. The spray mortar for repairing concrete structure according to claim 1, characterized in that: The fine aggregate is quartz sand, which is any one of machine-made sand, washed sand and river sand; the silicon dioxide content in the quartz sand is greater than 96%, the mud content is less than 0.2%, and the maximum particle size is 0.6 mm.
6. The spray mortar for repairing concrete structure according to claim 1, characterized in that: The admixture includes one or more of fly ash, silica ash, ultrafine fly ash, metakaolin and bentonite. The fly ash is primary or secondary low-calcium ash, the silica ash has a silicon dioxide content greater than 92%, and the bentonite is organic bentonite.
7. The spray mortar for repairing concrete structure according to claim 1, characterized in that: The modifier is a mixture of polysaccharide macromolecular polymer and nano silicon dioxide in a mass ratio of 2:1, or a mixture of polyacrylate resin and nano silicon dioxide in a mass ratio of 2:
1.
8. The spray mortar for repairing concrete structure according to claim 1, characterized in that: The additive is a mixture of melamine water reducer and one or more of other water reducers, wherein the other water reducers are naphthalene water reducer, sodium lignin sulfonate water reducer and calcium lignin sulfonate water reducer.
9. A method for preparing a spray mortar for repairing a concrete structure according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: firstly, uniformly mixing the modifier and the additive, and preparing an aqueous solution with a small amount of water for standby use; then, uniformly mixing the phosphate cement, the fine aggregate and the admixture by dry mixing; then, pouring in the remaining water and stirring for 2 to 3 minutes; finally, adding the aqueous solution and continuing to stir, so as to obtain the spray mortar.
10. A method for using the spray mortar for repairing concrete structures according to any one of claims 1 to 8, characterized in that: Before construction, clean the surface of the concrete structure or wall. Use a high-pressure water gun to wash away dust, moss, oil and other impurities on the surface and dry them. If the exposed steel bars are rusted, they should be derusted first, and then use a mortar sprayer to evenly spray the mortar on the surface of the structure.
Citation Information
Patent Citations
A non-flowing, fast-setting, high-bonding phosphate cement repair material and its preparation method
CN106966687B
An easy-to-apply, high-adhesion facade repair material and its preparation method
CN109592959B
Phosphorus-magnesium-based cement gunning material, and preparation method and application thereof
CN109694231A
Preparation method and application of phosphorus-magnesium-based cement concrete coating protective material
CN111333403A
Double-liquid magnesium phosphate material and preparation method thereof
CN111592328A